Borax analysis with spectrophotometry on meat bakso of frozen food that sold in modern markets and traditional markets in Palembang - Siti Rohani; Yanti Rosita; Vina Pramayastri; Lutfiah Hafidzah (Talenta Publisher, 2023)
Meatballs are one of the processed meat products that are in great demand by all levels of society. Along with the times and changes in public consumption trends, currently meatballs are turning into frozen food which is more simple and practical for cooking anytime. As processed frozen meat, making frozen food meatballs are often added with food additives (BTP) to maintain food quality such as preservatives, thickeners, and dyes. Borax is a dangerous chemical that is often added to food as a thickening agent. This study aims to determine and compare frozen food meatballs sold in modern markets and traditional markets in Palembang City which contain borax based on physical tests and to analyze borax levels using UV-Vis spectrophotometry. In this study, the maximum wavelength obtained to measure the absorbance of the 10 samples that have been prepared is 423,50 nm. Determination of the standard borax solution curve that has been made with various concentrations were 5 ppm, 10 ppm, 20 ppm, and 30 ppm. The obtained linear equation y = 0,0352x + 0,2047 with coefficient correlation (r) 0,9631. The levels of borax contained in the frozen food meatballs as the research samples were sample A contained 13,322 µg/ml, sample B contained 9,392 µg/ml, sample C contained 12,688 µg/ml, sample D contained 23,379 µg/ml, sample E contained 29,127 µg /ml, sample F was 24,821 µg/ml, sample G was 17,583 µg/ml, sample H was 15,595 µg/ml, the sample I was 26,665 µg/ml, sample J was 12,460 µg/ml. Based on physical tests, the characteristics of frozen food meatballs containing borax showed a brighter color, an unnatural smell, very chewy, and hard texture that is difficult to destroy. In conclusion, the ten samples of frozen food meatballs tested all contained borax with varying levels.